2016
DOI: 10.1016/j.eurger.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preventive home visits on older people's use and costs of health care services: A systematic review

Abstract: H. (2016) Effects of preventive home visits on older people's use and costs of health care services: A systematic review. European Geriatric Medicine, 7(6), 571-580. Sammendrag:Introduction: The aim of this study was to systematically review the evidence from randomized controlled trials (RCT) concerning effectiveness of preventive home visit (PHV) programs on older people's use and costs of health and social services. We also evaluated resultant costs-changes achieved with intervention in older people's funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…15 However, it is currently unclear which intervention components are most beneficial for older people with frailty. 16,17 Home-based interventions appear to be promising, with evidence suggesting that they can have beneficial effects on mortality, functioning and emergency department admissions, with neutral effects on costs. [16][17][18][19] Previous evidence supported interventions based on multidimensional geriatric assessment including follow-up visits.…”
Section: Clinical Frailty Scalementioning
confidence: 99%
See 1 more Smart Citation
“…15 However, it is currently unclear which intervention components are most beneficial for older people with frailty. 16,17 Home-based interventions appear to be promising, with evidence suggesting that they can have beneficial effects on mortality, functioning and emergency department admissions, with neutral effects on costs. [16][17][18][19] Previous evidence supported interventions based on multidimensional geriatric assessment including follow-up visits.…”
Section: Clinical Frailty Scalementioning
confidence: 99%
“…16,17 Home-based interventions appear to be promising, with evidence suggesting that they can have beneficial effects on mortality, functioning and emergency department admissions, with neutral effects on costs. [16][17][18][19] Previous evidence supported interventions based on multidimensional geriatric assessment including follow-up visits. 15 However, this type of intervention, typically with involvement from a multidisciplinary team of health and social care professionals, is expensive and difficult to deliver at scale, particularly if targeted at the larger group of up to 41% of older people with mild or pre-frailty living at home.…”
Section: Clinical Frailty Scalementioning
confidence: 99%
“…Therefore, preventive and proactive interventions supporting older people's health, functioning and well-being are needed. Preventive home visits (PHVs) for older people have been suggested as a means to enhance these goals, but the data on their effectiveness and cost-effectiveness are controversial [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a high number of trials exploring efficacy of PHVs [1], they are not easily comparable because of varying interventions, differing populations [2] and insufficient reporting and poor compliance [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A Finnish research team recently completed a systematic review of randomised controlled trials reporting use and/or costs of home visits on older people with multimorbidities. 4 Although six studies suggested that they may decrease nursing home admissions and/or hospital days, and seven studies showed some favourable effect on quality of life or mortality, no studies were able to show significant differences in total costs between intervention and control groups.…”
mentioning
confidence: 99%